2013
DOI: 10.2166/wst.2013.233
|View full text |Cite
|
Sign up to set email alerts
|

Removal of cadmium from water using by-product Crambe abyssinica Hochst seeds as biosorbent material

Abstract: The effectiveness of Crambe abyssinica Hochst seeds by-product as a biosorbent for the removal of cadmium ions from wastewater was analyzed. The biomass of crambe was characterized by scanning electron microscopy, infrared spectroscopy and determining the point of zero charge. The optimum adsorption conditions obtained were 400 mg of biomass in a solution of pH 6.0 and contact time of 60 min to remove 19.342 mg g(-1) cadmium ions. The isotherms of adsorption were constructed and, according to the mathematical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 2 publications
0
12
0
1
Order By: Relevance
“…Best contact time between adsorbent and adsorbate, which defines the minimum period required for equilibrium within the adsorption system to obtain maximum removal of Cu 2+ or Zn 2+ by the biosorbents studied in current research, is short. As a rule, longer contact time, sometimes up to 180 min, are necessary to obtain high removal rates [38][39][40]. The faster the effective removal of the adsorbate by the adsorbent, the better will be the material.…”
Section: Effect Of Contact Time Between Adsorbent and Adsorbed And Thmentioning
confidence: 99%
“…Best contact time between adsorbent and adsorbate, which defines the minimum period required for equilibrium within the adsorption system to obtain maximum removal of Cu 2+ or Zn 2+ by the biosorbents studied in current research, is short. As a rule, longer contact time, sometimes up to 180 min, are necessary to obtain high removal rates [38][39][40]. The faster the effective removal of the adsorbate by the adsorbent, the better will be the material.…”
Section: Effect Of Contact Time Between Adsorbent and Adsorbed And Thmentioning
confidence: 99%
“…10i-l). Meneghel et al (2013), Rubio et al (2013b), Coelho et al (2014) and Schwantes et al (2015) also found lower desorption rates for Cr 3+ , respectively, using the adsorbents: Moringa oleífera L., Crambe abyssina H., cashew nut shell, cassava peels in natura; all authors state the Cr is probably chemisorbed by the biomass. In most tests (Fig.…”
Section: Efficiency Of Adsorption and Desorptionmentioning
confidence: 92%
“…removal may be a short time. Longer contact periods are usually needed for high removal rates which may reach 180 min (Guo et al 2008;Argun and Dursun 2008;Witek-Krowiak et al 2011;Coelho et al 2014;Meneghel et al 2013a;Rubio et al 2013a). It should be underscored that a quick and effective removal of solution contaminants is highly important and desirable for biosorbents.…”
Section: Study On the Effect Of Contact Time Between Adsorbent And Admentioning
confidence: 99%